2010
DOI: 10.1007/s12052-010-0292-3
|View full text |Cite
|
Sign up to set email alerts
|

Creationism and the Teaching of Evolution in Poland

Abstract: For many years, the creationist movement in Poland was so marginal that the term "creationism" and its foundations were largely unknown within society. Nevertheless, at the end of the 1980s and beginning of the 1990s, the country underwent rapid political, economic, and sociological transformation. As part of the reaction, many ideas previously censored by the Communist regime became fashionable. This was also partly true for the creationist movement. However, creationism did not gain high acceptance within so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…This has rarely been done in biological anthropology classes where presumably human evolution is a core focus (though see Cunningham and Wescott, ), and I would argue that it is not overly arduous. Borczyk () noted that while creationists are very well organized, scientists often act independently from their colleagues in other countries (and I would add in other states or even adjacent communities), leaving us to build our anti‐creationist strategies from the ground up independently rather than joining forces and using evidence‐based tactics that are successful at least on some level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This has rarely been done in biological anthropology classes where presumably human evolution is a core focus (though see Cunningham and Wescott, ), and I would argue that it is not overly arduous. Borczyk () noted that while creationists are very well organized, scientists often act independently from their colleagues in other countries (and I would add in other states or even adjacent communities), leaving us to build our anti‐creationist strategies from the ground up independently rather than joining forces and using evidence‐based tactics that are successful at least on some level.…”
Section: Discussionmentioning
confidence: 99%
“…A study of elementary and secondary science teachers in Turkey, where the majority of the population is Muslim, found that those with a stronger understanding of the nature of science were more likely to both accept evolution and believe it is necessary to teach in evolution in their classrooms (Tekkaya et al, ). Anti‐evolution or intelligent design efforts relating to schools are on the rise in Northern Ireland (McCrory and Murphy, ), the United Kingdom (Williams, ), Poland (Borczyk, ), and other areas of Europe (Brem and Sinatra, ) as well as New Zealand (Campbell and Otrel‐Cass, ) and Brazil (Penteado et al, ).…”
Section: Obstacles To Teaching and Learning Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Szerszynski 2010: 164) Other scholars agree that education has a considerable impact on the distribution of creationist beliefs, but they sometimes differ in the type of influence it exerts. Ulrich Kutschera (2008a) and Bartosz Borczyk (2010), for instance, argue that creationism in Europe is on the rise because of the fact that religious education, which is often funded by the state and sometimes even compulsory in European countries, is provided much earlier than science education, thus shaping a receptive audience for creationist beliefs. James Williams (2008) Szerszynski (2010) in that the fact that most European education is under state control has a negative effect on the success of creationist beliefs.…”
Section: Explaining Creationism In Europementioning
confidence: 99%
“…Creationism in Turkey was already being discussed at length in the 1990s (Edis 1994(Edis , 1999; see also: Edis 2007;Hameed 2010;Riexinger 2008;Sayin and Kence 1999), as was creationism in the UK (Coleman and Carlin 1996). However, more detailed studies have recently become available, discussing creationism in Germany (Kutschera 2008a(Kutschera , 2008b, the United Kingdom (Williams, 2008), Russia (Levit, Hoßfeld and Olsson 2007), Poland (Borczyk 2010), Denmark (Hjermitslev 2010a) and the Netherlands (Blancke 2010, Flipse 2012.…”
Section: Introductionmentioning
confidence: 99%